Pirates in Print: Richard Hawkins’ Capture and the Origins of the Printing Press in Lima - Ríos Taboada, María Gracia (2024)
In 1594, the first news text was printed in Lima. The “Relación de lo sucedido desde diez y siete de mayo” narrated the triumphant armada sent by Viceroy García Hurtado de Mendoza and the subsequent capture of the English pirate Richard Hawkins. This article aims to delve into the motivations driving the urgency to disseminate this news, along with other documents linked to the event. Additionally, it will explore the nexus between these narratives and the propaganda campaign orchestrated by the Viceroy of Peru in its favor. As will be demonstrated, the presence of European adversaries in America not only intensified the intricate political landscape but also added complexity to the economic relations between Spain and its viceroyalties.